PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) DI KELAS IV SEKOLAH DASAR - rani, sastika; eliyasni, rifda; sukma, elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of comprehension reading skill by using Directed Reading Thinking Activity (DRTA) strategy for fourth grade students of SD Negeri 28Air Tawar Timur. Research subjects were teachers as observers, researchers, and fourth graders as many as 27 people consisting of 16 men and 11 women. In the first cycle, I obtained an average score of 60.6, an average reading rate of 75.0, and an average post-reading rate of 74.2. In cycle II the average value of prabaca 78.0, the average value of reading 84.3, and the average value of 85.1 post-reading. Thus reading comprehension with strategy (DRTA) can improve in class IV SD 28 Air Tawar Timur Kota Padang. Keywords: reading comprehension, directed reading thinking activity